Infantile Epileptic Encephalopathies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The phenotypic variability associated with sodium channel alpha 1 subunit gene SCN1A mutations was studied in 188 patients with various infantile epileptic encephalopathies referred to the Universities of Adelaide and Melbourne, Australia; and centres in Glasgow, UK; Wellington, New Zealand; Montreal and Vancouver, Canada; Worcester, MD, USA, Israel, and Denmark.